ANALISIS TINGKAT KETANGGUHAN BENCANA KELURAHAN KASTELA KOTA TERNATE (STUDI KASUS PANDEMI COVID 19) - Marwan, Marwan (Lembaga Penelitian dan Pendidikan Mandala, 2022)
The purpose of this study is to determine the readiness of the government in Kastela Village in dealing with any potential disasters that occur. This research was conducted with a qualitative approach, namely an approach model that is carried out to answer a phenomenon that occurs in the community by constructing it and then trying to trace the root of the problem based on the facts found. The results of the study revealed that, 1) The level of disaster resilience of Kastela Village is still very low so it has not yet entered the primary category. This is because almost all the aspects measured have not been met; 2) One very important aspect is that the legislation is assessed by respondents and it is even perceived that nothing has been done on all items measured so that it is given a value of 0. Whereas in this aspect it is considered as one of the bases for carrying out other aspects; 3) Other aspects are also categorized as very low, even some aspects are also explicitly given a score of 0, meaning that the government at the Kastela Village level has not done anything yet; 4) The level of resilience of the Kastela Village which has not been good has an impact on the handling of Covid 19. problems in the field. Even now, in the second year of this pandemic, it has not been able to run well. As in the vaccination program that has not run according to the government's target.